(untitled) (Global Journal of Human-Social Science, 2014)
Economic growth coupled with equitable distribution of income and low poverty levels are the prime objective of economists and policy makers Industrial sector has been the engine of growth in the process of growth and development of the developed economies of today Pakistan economy is the sixth largest economy of the world About 48 percent of population in Pakistan is living under multidimensional poverty The industrial sector of the Pakistan economy contributes about one-fifth of shares in the GDP It employs a large share of labor force So these facts provided the aspirations to explore the impact of manufacturing sector employment on multidimensional poverty in Pakistan Crosssectional data of 34 districts of Punjab province is used for the analysis Multidimensional poverty head count index is regressed on manufacturing sector employment healthcare and education service The standard OLS method is used to estimate the poverty equation The study confirms the poverty alleviating impact of manufacturing sector employment and human capital healthcare and education The estimated model qualifies the diagnostic specification error and stability tests The study also suggests some policy recommendations for the improvement of the human capital and manufacturing sector